IMPROVEMENT OF ENERGY CONSUMPTION IN COMPLIANCE TO ISO 50001 ENERGY MANAGEMENT SYSTEMS (CASE STUDY LIGHTING SYSTEMS AT PT BADAK NGL) - Prasetya, Yuda
The Badak LNG plant in Bontang Kalimantan Timur, Indonesia has been operating since 1974. By operating a 47 year old LNG plant and the technology used in natural gas liquefaction is relatively outdated, it will result in a decrease in performance and efficiency, which in turn will result in the Badak LNG plant being less competitive in the competition between Global LNG Plants. The results of the benchmarking operational performance review conducted by Phillip Townsend Associates Inc (PTAI) in 2018, obtained the fact that the percentage of energy usage used for LNG production activities at the Badak LNG plant was 12.0%, while the energy usage of the global LNG plant which was included in the age peer group with an age group of which is relatively the same as the Badak LNG plant is 9.1%. To pursue the energy usage efficiency gap, the Badak LNG plant implements an energy management system, engineering studies have been carried out to improve efficiency in several systems. Considering the operation of the Badak LNG plant, improvements will be made to lighting systems that meet the criteria of low investment cost but provide high return on investment and a short pay-back period. By using the current reality tree (CRT) and interviews with key stakeholders, the main cause of inefficiency in lighting systems is there is no updates to the lighting systems specification. Using the analytical hierarchy process (AHP), the best alternative solution to reduce energy consumption in lighting systems is retrofit to an LED bulb and install an occupancy sensor. This alternative will have the impact of reducing energy consumption by 6.924 MW/year or the equivalent of cost saving USD 1,315,599/year. And total energy usage decrease by 0,52%